2021
DOI: 10.1111/jocn.15803
|View full text |Cite
|
Sign up to set email alerts
|

Improving hypertension knowledge, medication adherence, and blood pressure control: A feasibility study

Abstract: Aims and Objectives:To examine the feasibility of a culturally tailored education programme for Haitian immigrants diagnosed with hypertension.Background: Hypertension is a major public health problem, impacting more than 26% of the global population. The overall prevalence of hypertension is 45.4% in the United States with nearly 80,000 deaths due to hypertension in 2015. African Americans and other Black populations living in the U.S. are disproportionally affected by hypertension.Design: Pre-test and post-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…The higher prevalence of hypertension among foreign-born than non-immigrant Australians could be due to the increase in the prevalence of hypertension in low-and middle-income countries [124]. There was a significant lowering of blood pressure, an increased knowledge of hypertension and greater compliance with medical treatment six weeks after the intervention [125]. Therefore, the high rates of hypertension among foreign-born populations from those countries may merely reflect the rising rates in the participants' countries of origin.…”
Section: Discussionmentioning
confidence: 99%
“…The higher prevalence of hypertension among foreign-born than non-immigrant Australians could be due to the increase in the prevalence of hypertension in low-and middle-income countries [124]. There was a significant lowering of blood pressure, an increased knowledge of hypertension and greater compliance with medical treatment six weeks after the intervention [125]. Therefore, the high rates of hypertension among foreign-born populations from those countries may merely reflect the rising rates in the participants' countries of origin.…”
Section: Discussionmentioning
confidence: 99%
“…Each question has one point. Participants were categorized based on points to low (<6), moderate [ 6 , 7 ], and high [ 8 ] adherence groups. The validity and reliability of MMAS-8 were tested and verified in a previous study [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Multiple factors could affect medical and nonmedical adherence, such as age, race, social support, anxiety, and depression [ 7 ]. Proper management for HTN is reachable within the accompany of patients and health care providers [ 8 ]. Self-care is defined as the capabilities of patients and communities to involve in the activities related to health promotion and disease prevention and management.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, researchers used outcome measures adapted for use with African Americans (e.g., Community Healthy Activities Model Program for Seniors physical activity questionnaire modified for African Americans and an adaption of Food Habits Questionnaire for participants) [52,111]. Others reported that the outcome measure was reliable and validated for use by this community [94,119]. See Supplementary Material 4 details the outcome measures used in each study.…”
Section: Program Outcomesmentioning
confidence: 99%